Risks of derivative financial instruments in the activities of commercial banks - O.A.; О.S.; G.L. (Економіка, управління та адміністрування, 2023)
The evolution of derivative financial instruments opens up new opportunities for commercial banks and other companies to manage risks and obtain other economic benefits. Derivative financial instruments have not become widespread in Ukraine due to deficiencies in legal regulation and the lack of relevant specialists. In recent years, within the framework of the Association Agreement with the EU, the provisions of more than thirteen acts of the European Union legislation in the area of regulation of capital markets have been implemented into national legislation. This regulated the legal basis for transactions with derivative financial instruments and creates favorable conditions for their use. However, derivative financial instruments are intricate in their nature and are often accompanied by risks that are not always objectively assessed and lead to significant losses in banking activities. For a long time, there have been discussions in scientific circles about the need to strengthen the regulation of transactions with derivative financial instruments due to their risks in the activities of banking and other financial institutions. The study analyzed the risks of derivative financial instruments and systematized them by management level. In particular, market risk, liquidity risk, counterparty risk, operational risk and legal risk of derivative financial instruments are under the management of the commercial bank that uses them. Systemic risk has a more complex nature and affects the entire banking system and the financial system as a whole, therefore it is under the control of the central bank. The study draws attention to the fact that systemic risk cannot be minimized through effective risk management of derivative financial instruments at the level of individual banks. Although commercial banks are elements of the banking system, they operate in a competitive environment among themselves. Therefore, in the event of financial shocks, they will take care of their own interests, and not the preservation of the stability of the banking system.